2016
DOI: 10.1021/acs.organomet.6b00757
|View full text |Cite
|
Sign up to set email alerts
|

Alkene Insertions into a Ru–PR2 Bond

Abstract: An unusually broad series of discrete alkene insertion reactions has provided the opportunity to examine the mechanism(s) of this fundamental carbon−heteroatom bondforming process. Ethylene, electron-rich and electron-poor (activated) alkenes all react with the Ru−P double bond in Ru(η 5 -indenyl)(PCy 2 )(PPh 3 ) to form κ 2 -ruthenaphosphacyclobutanes. Thermal decomposition of these metallacycles in solution, via alkene deinsertion and β-hydride elimination, is particularly favored for electron-rich alkenes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Rosenberg's systems, commonly (indenyl)(PPh 3 )Ru=PRR’, possess significantly different ligands, with respect to electronic effects, than the Cp and CO ligands of 2 . Moreover, Rosenberg's compounds are coordinately unsaturated and exhibit substantial phosphorus‐to‐metal π bonding . The relationship between these compounds is significant nevertheless, and an insertion‐based mechanism is the working hypothesis here.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Rosenberg's systems, commonly (indenyl)(PPh 3 )Ru=PRR’, possess significantly different ligands, with respect to electronic effects, than the Cp and CO ligands of 2 . Moreover, Rosenberg's compounds are coordinately unsaturated and exhibit substantial phosphorus‐to‐metal π bonding . The relationship between these compounds is significant nevertheless, and an insertion‐based mechanism is the working hypothesis here.…”
Section: Resultsmentioning
confidence: 92%
“…The literature provides some useful indications of a likely mechanism. Rosenberg and coworkers provide excellent evidence in support for a concerted, inner‐sphere (e. g., insertion) reaction of alkenes at the Ru−P bond of related indenyl ruthenium phosphido compounds . That precedent provides a strong basis for a mechanistic hypothesis that involves insertion into a Ru−P bond in this system.…”
Section: Resultsmentioning
confidence: 92%
“…RX or Michael-type alkenes) or inner-sphere migratory insertion processes . Our studies of phosphido complexes of a ruthenium indenyl half-sandwich fragment have demonstrated both inner- and outer-sphere reactivities, and we have reported the activity of this system for the catalytic hydrophosphination of activated alkenes, which apparently relies on outer-sphere P–C bond formation …”
Section: Introductionmentioning
confidence: 87%
“…Metal–phosphido bonds can be exploited for a variety of uses including hydrophosphination catalysts, small-molecule activation, and advancing our knowledge of their interactions with electropositive metals . A key observation in hydrophosphination is that the reactivity of metal–phosphido complexes involves the basicity of the phosphido ligand. For example, (η 5 -indenyl)­Ru­(PPh 3 )­(Cl)­(HPR 2 ), R = Cy, i Pr has the ability to catalyze the hydrophosphination of substituted alkenes, initially forming a reactive ruthenium phosphido complex upon deprotonation of the phosphine …”
Section: Introductionmentioning
confidence: 99%